Increasing the efficiency of the local budgets’ expenditures in context of the budget reform in Ukraine - Iuliia Ostrishchenko (Економічний вісник університету, 2016)
The study is the disclosure of problems and weaknesses planning expenditures of local budgets, identifying areas of improvement to increase efficiency of budget funds. Research methods. The paper used a set of scientific methods and approaches, including systemic, structural, comparative, factorial methods which allowed the realising conceptual integrity of the study. Results. Background and ways to improve planning and performance approaches for local budgets, in particular their expenditures are examined in the article. It is justified expediency of program budgeting and gender budgeting introduction in the budget process at the local level as a tool for improving the efficiency and transparency of the budget funding. Field of the results application. Local budgets. Local budgets formation in the financial and economic regulation system. Conclusions. Modern realities of the system of local budgets indicate a lack of effective approaches to planning and implementation. This particularly applies to management decisions when managers focus attention not on the efficiency of public spending, and the volume of resources used and the need for network maintenance budget organizations in need of optimization. In this study, necessity of the use of program-target method and gender budgeting and gender analysis in the planning and execution of local spending that will increase the efficiency and transparency of budget funds to ensure their fair distribution among different groups of recipients of public services.